EATING STYLE AND THE NATURE OF FOOD CONSUMPTION: MAPPING INDIVIDUALS’ HEALTH RISKS - Madihah Shukri; Nor Farid Mohd Noor (Malaysian Journal of Public Health Medicine, 2017)
Research examining whether psychological eating style is related to healthy or unhealthy eating patterns is required to explain the mechanisms underlying non-communicable diseases and obesity. The purpose of this study was to investigate whether eating style predicts thenature of food consumption. This was a cross-sectional study of 588 adults (males = 231 and females = 357). Eating style (i.e. restrained, emotional, external eating) was measured using the short version of the Dutch Eating Behaviour Questionnaire (DEBQ). The nature of food consumption was assessed using self-reports of consumption of fruits and vegetables, sweet foods, junk food, and snacks.The results revealed that restrained eating was higher in females and overweight participants. External eating,a higher frequency of snacking,and a higher frequency of junk food consumptionwere more prevalent among the younger participants. Consistent with previous Western studies, emotional eating was found to be the main predictor of consumption of less healthful foods (sweet foods, junk food, and snacks), whereas external eatingpredicted the intake of sweet foods. The intake of fruits and vegetableswas associated with restrained eating. In light of the significant associations between eating style and the nature of food consumption, acknowledging individuals’ eating styleshas implications for tailoring effective nutritional programs that address obesity and the chronic disease epidemic.